Effects of In-Band Crosstalk in Wavelength-Locked Fabry-Perot Laser-Diode-Based WDM PONs - Kim, Chul Han; Lee, Kwanil; Lee, Sang Bae (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2009)
We investigated the impact of in-band crosstalk on the system's performance in wavelength-locked Fabry-Perot laser-diode (FP-LD)-based wavelength-division-multiplexed passive optical networks (WDM PONs). As expected, wavelength-locked FP-LD, which was injected by using an incoherent broadband light source, was more tolerant to in-band crosstalk than distributed-feedback (DFB) laser diode. A 1-dB power penalty in the wavelength-locked FP-LD-based PON system was observed when the crosstalk-to-signal ratio was similar to-9 dB. We also compared the measured power penalties with the calculated power penalties. It has been shown that the in-band crosstalk-induced power penalty in wavelength-locked FP-LD-based WDM PON could be estimated properly by taking into account both effects of power addition and signal-crosstalk beat noise.
Keywords: TRANSMISSION; REFLECTION; PENALTIES; SYSTEMS; IMPACT; NOISE